On the performance of distributed space-time coding systems with one and two non-regenerative relays - Anghel, P.A.; Kaveh, M. (IEEE transactions on wireless communications, 2006)
Spatial diversity can be induced by using wireless relay stations, which cooperate by amplifying and retransmitting the information received from a source to a destination station. In this context we propose a distributed space-time coding (DSTC) system based on the Alamouti codes. We characterize the symbol error rate of systems with one and two non-regenerative relays using bounds and high signal-to-noise ratio (SNR) approximations. The asymptotic (high SNR) symbol error probability formulas are used to optimize the power allocation in the DSTC system. Furthermore, using the asymptotic symbol error probability formulas we argue that the DSTC system has at least 1.5 times the diversity achieved by point-to-point transmissions with the same bandwidth. Simulations show not only that the DSTC outperforms the amplify-and-forward cooperative system with orthogonal transmissions, but also convolutional encoded one-hop transmissions with the same information rate as the DSTC system. Assuming full channel knowledge at the source and the relays, we find an optimum cooperative system by minimizing the bit error rate of the DSTC system with one and two non-regenerative relays subject to fixed transmit energy constraints at each radio. Numerical results show that the DSTC system with two relays performs very close to the optimum cooperative system.